The dangers of illiteracy and its negative effects on development and its health, civilizational and cultural dimensions in the Kingdom of Saudi Arabia - Al-Khaldi, Fawzia Hamdan; Al-Mobeeriek, Haifa Fahad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to investigate the dangers of illiteracy and its negative effects on development and its health, civilization and cultural dimensions in the Kingdom of Saudi Arabia. The study used the descriptive analytical method by analyzing the relevant literature. The study consisted of three detectives; The first topic dealt with the dangers of illiteracy and the second dealt with the negative effects of illiteracy on development, while the third included: the health, civilizational and cultural dimensions of illiteracy. The study concluded that illiteracy constitutes an obstacle to achieving sustainable development and the cultural, civilizational and health enlightenment of society and individuals. The study made several recommendations, the most important of which are activating programs to eradicate that illiteracy, achieve equity and assimilation, and help alleviate poverty, combat diseases, educate and urbanize, and build societies based on knowledge and characterized by the ability to sustain development.
Keywords: Illiteracy Risks; Illiteracy Effects; Development; Illiteracy Dimensions; Health Dimensions; Civilizational Dimensions; Cultural Dimensions